"Education against the Grain": Examining the Evolution of Media Archival Training at UCLA. Issue 3 (2nd October 2018) - Naveh, Jonathan
Abstract: This essay broadly analyzes the history and current state of media archival education through a case study of two graduate degrees previously and currently offered at UCLA: the interdepartmental Moving Image Archive Studies (MIAS) MA degree and the MLIS degree with specialization in Media Archival Studies.